A Rare Case of Concomitant Intramedullary Gangliocytoma at the Cervicomedullary Junction in Patient with Neuroendocrine Tumor of Lung - Aydemir, Fatih (J Korean Neurosurg Soc, 2016)
Ganglion cell tumors (GCT) are divided into two subtypes : gangliocytoma and ganglioglioma. Intramedullary gangliocytomas are extremely rare. A 20-year-old male patient with pain of neck, who also had a previously known neuroendocrine tumor of lung, was operated for mass found in the cervicomedullary junction with a presumptive diagnosis of metastases. Only partial resection could be performed. Pathological diagnosis had been reported as gangliocytoma. Only ten cases of intramedullary gangliocytoma have been reported in the literature. Although association with scoliosis and Von Recklinghausen's disease were previously reported in the literature, no gangliocytoma case concomitant with endocrine tumor of lung have been published. Pathological study is the most important diagnostic method for gangliocytomas. Surgical excision is the primary treatment, but difficulty in total surgical tumor resection is the most important problem.